The territory from rio das Fêmeas: considerations on environmental management in São Desidério, State of Bahia, Brazil (Research, Society and Development, 2020)
Rio das Fêmeas, their multiple uses and their surroundings, constitute a relevant place to be considered for the understanding of territorial ordering and management by the State of Bahia due to the complexity of the relationship between environment and society and the direct influence of the management of the River Basin Grande and its territory in the maintenance of the Urucuia Aquifer System and the São Francisco River. The objective of this work was to discuss this interwoven and complex interrelation in the West of Bahia, from the municipality of São Desiderio, where Rio das Fêmeas has its source and mouth, being a means of production to the agribusiness production chain, influencing the state management process that territory. This is qualitative exploratory research, with documentary analysis (national, state and municipal legislation; environmental management and water resources), secondary data collection (area and production of the main agricultural activities) and observations with on-site visits, focusing on - territorial management and socio-environmental issues surrounding the Rio das Fêmeas. It was observed that the current model for the exploration of agribusiness (irrigation; suppression of vegetation; intensive cultivation)) and energy generation (SHPPs) of the Rio das Females produces negative impacts in the Rio Grande Basin and, by extension, in the Urucuia Aquifer System , characterizing depletion of surface water reserves, from the water recharge system, flow, water and soil pollution, consequent quality of life of the population, by the dynamics of the system of actions that constitutes Territory Management with government and non-state policies.